Poorly Differentiated Thyroid Carcinoma Arising in Struma Ovarii - Surapan Khunamornpong; Jongkolnee Settakorn; Kornkanok Sukpan; Prapaporn Suprasert; Sumalee Siriaunkgul (Hindawi Limited, 2015)
Struma ovarii is an uncommon type of ovarian mature teratoma with a predominant thyroid component. The morphological spectrum of the thyroid tissue ranges from that of normal thyroid to proliferative adenoma-like lesions and thyroid-type carcinomas (malignant transformation). The histologic features of ovarian strumal lesions sometimes cause diagnostic problems due to the confusion with other types of ovarian neoplasms and the difficulty in the prediction of their clinical behavior. We report an extremely rare case of poorly differentiated thyroid carcinoma arising in struma ovarii. A 22-year-old woman presented with a 15 cm right ovarian mass. The tumor showed a predominantly tubular pattern which raised a differential diagnosis between endometrioid adenocarcinoma and Sertoli cell tumor. A review of the gross specimen with additional tissue sampling helped identify the teratomatous and strumal nature, with a support by immunohistochemical staining. Despite FIGO stage IA by optimal staging procedure and the absence of identifiable lymphovascular invasion, the patient developed pulmonary metastasis 15 months after surgery and died from the progression of the disease 7 years after the diagnosis. This case emphasizes the importance of macroscopic examination of the specimen and the awareness of this uncommon tumor in the differential diagnosis of ovarian neoplasms.